Psychological capital, leader-member exchange, and job involvement in shaping innovative behavior and work habits: Evidence from a non-banking financial entity in Jawa and Papua - Mustajab, Duta; Darmayanti, Novi (Goodwood Publishing, 2024)
Purpose: This study examines the influence of psychological capital, leader-member exchange, and job involvement on employees’ innovative behavior and work habits in the context of organizational transformation. Methodology: Using a sample of 403 employees from a state-owned Non-Banking Financial Entity (NBFE) operating across Jawa and Papua provinces, the study analyzes how individual and relational factors contribute to developing sustainable work practices, with innovative behavior as a mediating variable. Structural equation modeling with bootstrapping was applied to test the hypothesized relationships. Results: The results show that psychological capital and job involvement significantly enhance innovative behavior, which in turn positively affects employees’ work habits. Innovative behavior also mediates the relationship between psychological capital and job involvement with work habits. In contrast, leader-member exchange demonstrated a direct positive effect on work habits but no significant effect on innovative behavior or its mediating pathway. These findings highlight the pivotal role of employees’ psychological resources and engagement in fostering creativity and consistent, adaptive work behavior, while underlining the need for context-sensitive leadership strategies. Limitations: This study is limited by its focus on a single non-banking financial organization, which may affect the generalizability of the results to other sectors. Additionally, cultural differences between Java and Papua may influence perceptions of leadership and organizational behavior, requiring careful contextual interpretation. Contribution: The study contributes to the organizational behavior literature by providing empirical evidence on the mechanisms linking individual and organizational factors to sustainable employee performance in a culturally diverse and transforming financial institution.